2008
DOI: 10.1007/s11671-008-9173-x
|View full text |Cite
|
Sign up to set email alerts
|

Hot Photoluminescence in γ-In2Se3Nanorods

Abstract: The energy relaxation of electrons in γ-In2Se3nanorods was investigated by the excitation-dependent photoluminescence (PL). From the high-energy tail of PL, we determine the electron temperature (Te) of the hot electrons. TheTevariation can be explained by a model in which the longitudinal optical (LO)-phonon emission is the dominant energy relaxation process. The high-quality γ-In2Se3nanorods may be a promising material for the photovoltaic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…EDS composition study of the as-grown γ-In 2 Se 3 thin film is shown in Fig. 3(c), which demonstrates the presence of In and Se.Figure4(a) presents the 532 nm laser-illuminated PL spectrum of the γ-In 2 Se 3 film with PL peak positioned at 1.94 eV, which is in good agreement with the previous literature [31][32][33]. The existence of PL spectrum depicts the production of photo-induced charge carriers, which is a vital property of semiconductor material for its application in optoelectronic/photovoltaic devices.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…EDS composition study of the as-grown γ-In 2 Se 3 thin film is shown in Fig. 3(c), which demonstrates the presence of In and Se.Figure4(a) presents the 532 nm laser-illuminated PL spectrum of the γ-In 2 Se 3 film with PL peak positioned at 1.94 eV, which is in good agreement with the previous literature [31][32][33]. The existence of PL spectrum depicts the production of photo-induced charge carriers, which is a vital property of semiconductor material for its application in optoelectronic/photovoltaic devices.…”
supporting
confidence: 86%
“…Figure 4(a) presents the 532 nm laser-illuminated PL spectrum of the γ-In 2 Se 3 film with PL peak positioned at 1.94 eV, which is in good agreement with the previous literature. [31][32][33] The existence of PL spectrum depicts the production of photo-induced charge carriers, which is a vital property of semiconductor material for its application in optoelectronic/photovoltaic devices. As a proof-of-concept, a simple device is fabricated by manually pasting two In-Ga eutectic alloy electrodes to the two sides of the short edges of a 200 nm thick γ-In 2 Se 3 epifilm (with plane geometry of 10 mm × 4.5 mm), respectively, to inspect the optoelectronic response under the illumination from a standard sun solar simulator (AM 1.5 G, 100 mW/cm 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several different methods have been demonstrated to grow In 2 Se 3 epilayers, such as evaporation [5,6], the Bridgman-Stockbarger Method [7,8], and metal-organic chemical vapor deposition (MOCVD) [9][10][11]. Recently, one-dimensional III-VI semiconductor nanostructures, such as nanowires and nanotubes, exhibited novel and device applicable physical properties, which can be used in a wide variety of applications in nanoelectronic and nanooptoelectronic devices [12][13][14][15][16][17]. For example, α-phase layerstructured In 2 Se 3 nanowires have been grown and have shown a large anisotropy in both structure and conductivity [12].…”
mentioning
confidence: 99%
“…In our previous work, energy relaxation of hot electrons in γ-In 2 Se 3 nanorods has been investigated [16]. It was found that the main path of energy relaxation for the hot electrons is LO-phonon emission.…”
mentioning
confidence: 99%
See 1 more Smart Citation